The Barcelona olympic experience 1986-1992 and the Forum 2004 expectations (Ciudades, 2018)
The present article deals mainly with the economic impacts of the Olympic Games, especially with those associated with the infrastructure project and urban development. It is showed the principie projects in relation with the Olympic Games of 1992, and the more inmediate economic impact on the city and the metropolitan area. The future event designed to concentrate efforts and to project the city from a cultural point of view, the Forum 2004, is explained in the last part of the article. To close the article the most important conclusions are studied, analysing as strong points the effects of the global-cultural (Barcelona in the world map), the urban transformation through an infrastructure project, the consensus among public administrations and the partnership public-private. The weakness were the increase in the housing prices, the overestimation of the office demand and the limited public transport investments.
Keywords: Barcelona 92; Forum 2004